Meningkatkan Aktivitas Belajar dan Hasil Belajar Siswa dengan Penerapan Model Pembelajaran Explicit Intruction - Maimunah - (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2016)
On the XI grade students of APK2 at SMK Muh. 5Kepanjen , it is known that they have low achievement. The research finding showed that the Explicit Intruction learning model is able to make students to be active and creative as well as helping students to improve their learning activities and outcomes of make the Document/Stenography. This can be seen based on the value of learning activities that is observed by 3 observers. The average value of student activity before the given action was only lower 70with criterion C (enuogh). Furthermore, the average value of the class in the first cycle after the implementation of Explicit Intruction learning model increased to be above 70 with B (good) criterion. In the first cycle, the average value increased student learning activities for LKS to be 87,2 and 78 for LKR, the average value of formatif test is 86,5 and 77,6 for semester test with B (good) criterion. While students learning activities after the given action for 75% from 38 students has been active in learning. The students also increased during the study.Abstrak: Siswa di kelas XI APK 2 SMK MUH 5 Kepanjen, diketahui bahwa nilai aktivitas belajar dan hasil belajar siswa rendah. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran Explicit Intruction mampu menjadikan siswa aktif dan kreatif serta membantu siswa untuk meningkatkan aktivitas belajar dan hasil pelajaran Membuat Dokumen/Stenografi. Hal tersebut terbukti pada nilai aktivitas belajar yang diamati oleh 3 orang pengamat. Nilai rata-rata aktivitas belajar siswa sebelum diberi tindakan di bawah 70 dengan kriteria C (cukup). Selanjutnya nilai rata-rata kelas pada siklus I setelah adanya penerapan model pembelajaran Explicit Intruction meningkat menjadi di atas 70 dengan kriteria B (baik). Pada siklus I nilai rata-rata hasil belajar siswa meningkat menjadi rata-rata untuk LKS 87,2 LKR 78 ,nilai rata-rata ulangan harian 86,5 dan rata-rata nilai ulangan semester 77,6 dengan kriteria B (baik).Sedangkan aktivitas belajar setelah tindakan 75% dari 38 siswa telah aktif dalam pembelajaran. siswa juga mengalami peningkatan selama penelitian.